Pengejawantahan Daur Ulang Limbah Jelantah: Lokakarya Berbasis Model ADDIE Melalui Reka Cipta Lilin Aqualume Sebagai Upaya Pemberdayaan Kelompok PKK di Desa Sriwulan, Kabupaten Kendal - Charalli, Setyawati; Nasikha, Aulia; Wibowo, Mochammad Eric Suryakencana; Oktavia, Vicky; Cahya, Handy Nur (Sasambo: Jurnal Abdimas (Journal of Community Service), 2026)
form of used cooking oil that threatens the village's tourism image. Although the PKK Group handles used cooking oil waste at the household level daily, as frontline actors they lack the skills to transform it into valuable products. This activity aims to empower the PKK Group through increased knowledge about the impacts of used cooking oil, circular economy, and appropriate technology; enhance the technical skills of all participants (13 people) in producing Aqualume candles through hands-on practical learning; process 350ml of used cooking oil waste into 7 units of aesthetically quality eco-friendly souvenir products as creative enterprises supporting the tourism village; and implement the ADDIE model to ensure program effectiveness and sustainability. The implementation method uses ADDIE (Analysis, Design, Development, Implementation, Evaluation), which includes needs mapping, appropriate technology design, and practical workshops. Evaluation was conducted using pre-test and post-test to measure cognitive understanding and observation of product outcomes. The activity results showed a significant increase in participants' average scores from 40.00 to 100.00 with an N-Gain of 1.00 (high category). All 13 participants mastered the techniques of used cooking oil purification and aesthetic Aqualume candle formulation. This activity demonstrates that the ADDIE model effectively transfers appropriate technology, enhances community learning agility in adopting circular economy innovations, and produces distinctive eco-friendly souveniraq for the tourism village.